What we leave behind from Jean-Luc Godard's archive - Baecque, Antoine de 1962- (Libraryman, 2021)
"Subsequent to a commissioned sound composition for Deutschlandradio, multidisciplinary artist Stéphan Crasneanscki (b. 1969, French) further examines his significant opus What We Leave Behind, on French film director Jean-Luc Godard?s archive, into book form. The book is divided into four comprehensive sections: boxes, collages, still lifes and notes.0When invited to explore the archive of the seminal film director, Crasneanscki photographed Godard?s personal collection of shot film, reel-to-reels and historical ephemera. The notes and references in the book attest to the passing of time, yet being saved from oblivion; as a fragmented creative map of a master film director?s artistic thought process. In addition to working with someone?s personal belongings and its cultural heritage, Crasneanscki also adds his own interpretation and admiration to the material?s constellation of ideas of identity, traceability, temporality, space, memory, existence, materiality and historicity. The book contains a foreword by musician, author and poet Patti Smith (b. 1946, American), a conversation with filmmaker Abel Ferrara (b. 1951, American) and an essay written by film critic, historian and editor Antoine de Baecque (b. 1962, French)"
Keywords: Godard, Jean-Luc -- 1930-2022; Archiv; Fotografie; Godard, Jean-Luc / 1930-2022 / Archives / Pictorial works; Crasneanscki, Stéphan; Photography, Artistic; Photography of art; Pictorial works; Bildband